Examining Teachers' Views on Innovative Behaviour: A Comparative Study of Gender-Based Differences - Daulay, Dudy Faisal; Abdullah, Zuraidah (Proceedings Series of Educational Studies, 2024)
As organisations, schools require innovation to persist in a dynamic educational landscape. Innovation stems from the innovative behaviour of schools' members, including teachers, who play a crucial role in the innovation process. Previous studies have identified teacher gender as an influencing factor on innovative behaviour; however, several others have found no correlation between gender and innovative behaviour. Consequently, this study aimed to elucidate the phenomena occurring within the study population. Verifying this, a quantitative study was conducted on 160 high school teachers, comprising 80 male and 80 female teachers in Indonesia. The statistical analysis results indicate that teachers' perceptions of innovative behaviour are high. Furthermore, the findings reveal an insignificant difference in the perceptions of innovative behaviour between both groups. This outcome corroborates that gender is not a determining factor in how teachers perceive innovation in education.